NAHDLATUL ULAMA (NU) SEBAGAI CIVIL SOCIETY DI INDONESIA - Esty Ekawati (Research Institute and Community Engagement of IAIN MADURA, 2016)
Civil Society is non-government organization or an autonomous group which is faced with state and has a function for check and balance for the government policy. Civil society also has a function to social control. Lary Diamond said that civil society establish on cultural organization such as religion or ethnic or organization which keep the truth and believe. Nahdhatul Ulama is a religion organization in Indonesia which has function to social control for the government. Beside that, the activities of NU in education, democracy development and other social activities made NU still exist in social and political society in Indonesia.